(untitled) (JURNAL ADMINISTRASI PUBLIK, 2019)
As the executor of development and state administrators, the government in this case employees (ASN and THL) is obliged to protect (to protect the people), serve (to serve the people), and regulate (to regulate the people) all of which are "service delivery or public service ", in the context of fulfilling public interests (public interest) and addressing public affairs. The government needs to understand with certainty what its the role is in public service, how to realize service quality (Servqual) that satisfies the people as recipients of services, and how attitudes should behave as the government (Surjadi, 2009). According to Sinambela (2010), every human being needs service, even in the extreme it can be said that service cannot be separated from human life. Therefore, the services / public services provided to the public require certain qualities. The service provided by the management through its apparatus, even though it is not aimed at seeking profit, must still prioritize the quality of service in accordance with the demands, expectations, and needs of the people served. In an increasingly critical community condition, public bureaucracy is demanded to be able to change its position and role (revitalization) in providing public services. From those who like to rule and rule to being like serving. From those who like to use the power approach, it turns to be helpful to be flexible, collaborative, and dialogic. From slogan ways to pragmatic realistic ways of working. Keyword: Human Resources, Performance, Work Culture, Public Services